Ediorial: a new age for radio and sound studies - Oliveira, Madalena (2016)
The creation of a Radio Research Section within ECREA, as well as other groups and research projects, confirms “the sign of the revival of academic interest in radio” spotted by Peter Lewis in an article published by the International Journal of Cultural Studies (2000, p. 160). There is, among researchers particularly enthusiastic for audio production, a common feeling that radio has always been neglected by communication and media studies, which is quite true. For decades after the first studies on propaganda and public opinion performed by authors like Paul Lazarsfeld, communication research developed side by side with the increase of visual media and therefore was much more concerned with image than with sound. As a result, significantly more scientific discourse took place regarding television than regarding radio. The emergence of the screen quickly blinded audiences to the magic of radio and the power of imagination such a medium played in the first half of the 20th century was consigned to a marginalised idea of nostalgia in modern media societies.